Compressive behavior of FRP-wrapped seawater sea-sand concrete with a square cross-section. (30th November 2020) - Zeng, Jun-Jie; Duan, Zhi-Jian; Gao, Wan-Yang; Bai, Yu-Lei; Ouyang, Li-Jun
Highlights: Compressive behavior of PET FRP/CFRP-wrapped SSC in square columns was investigated. The type and thickness of FRP jackets and the blending water of SSC were test variables. The accuracy of typical confinement models for FRP-wrapped square concrete columns was examined. Abstract: Seawater sea-sand concrete (SSC) has attracted increasing attention as an alternative to normal concrete due to unsustainable usage and overexploitation of resources (e.g., gravel and river sand). The high chloride content of SSC has hindered its widespread applications since the conventional steel reinforcement is easy to be corroded by the abundance of chloride ions in SSC. Fiber-reinforced polymer (FRP) composites that are exempt from most corrosion problems have been introduced in the construction of SSC members. This paper presents a series of axial compressive tests on the square SSC columns wrapped with carbon and polyethylene terephthalate (PET) FRP jackets, the latter of which are cost-effective and environmentally friendly and have a large rupture strain (LRS). The experimental program included the axial compressive tests on 36 square columns wrapped with PET-FRP or CFRP jackets and 9 control cylinders. Based on the axial compressive tests, the effects of the SSC mixing water as well as the type and layers of FRP jackets were carefully investigated. The measured stress–strain curves of the column specimens were compared with the predictions by existing concrete confinement models to examine their reliability in predicting the compressive behavior of CFRP/PET FRP-wrapped square SSC columns.